Polymyxin Resistant Bacteria in Australian Poultry - Bean, David C.; Wigmore, Sarah M.; Abdul Momin, Muhd Haziq F.; Wareham, David W. (Frontiers in Sustainable Food Systems, 2020)
Resistance to last-resort antibiotics is significant public health issue. Antibiotic use in animal husbandry may be a driver of resistance that can subsequently be disseminated via the food chain. This study sought to determine the level of polymyxin resistance in Gram-negative pathogens present in Australian poultry, particularly the presence of mobilizable mechanisms of polymyxin resistance. Cloacal swabs from 213 birds were taken in a point prevalence survey from six different farms at a Victorian chicken processing facility. Colistin resistant organisms were recovered by direct plating on CHROMagar COL-APSE media. Bacterial isolates were identified and analyzed by MALDI-TOF, biochemical and genotypic assays. The 213 specimens yielded 57 (26.8%) colistin-resistant Gram-negative organisms, all of which have been previously described as exhibiting intrinsic resistance to polymyxin antibiotics. The most frequent organism was identified as Hafnia paralvei (40/57; 70%). Other colistin-resistant organisms included Aeromonas hydrophila (16%), Myroides odoratus (7%), Alcaligenes faecalis (5%), and Pseudochrobactrum spp. (2%). No mobile colistin resistance (mcr) genes were detected, although the arnA gene was identified in two A. hydrophila isolates and may mediate colistin resistance in these isolates. Intrinsic polymyxin-resistant organisms are widely distributed in the food chain, with over a quarter of the birds tested yielding a polymyxin-resistant organism. However, strains containing mcr genes remain rare in Australian poultry.